Enhancing the Therapeutic Potential of Mesenchymal Stem Cells with the CRISPR-Cas System - Filho, Daniel Mendes; de Carvalho Ribeiro, Patrícia; Oliveira, Lucas Felipe; dos Santos, Ana Luiza Romero Terra; Parreira, Ricardo Cambraia; Pinto, Mauro Cunha Xavier; Resende, Rodrigo Ribeiro (Stem cell reviews, 2019)
Mesenchymal stem cells (MSCs), also known as multipotent mesenchymal stromal stem cells, are found in the perivascular space of several tissues. These cells have been subject of intense research in the last decade due to their low teratogenicity, as well as their ability to differentiate into mature cells and to secrete immunomodulatory and trophic factors. However, they usually promote only a modest benefit when transplanted in experimental disease models, one of the limitations for their clinical application. The CRISPR-Cas system, in turn, is highlighted as a simple and effective tool for genetic engineering. This system was tested in clinical trials over a relatively short period of time after establishing its applicability to the edition of the mammalian cell genome. Similar to the research evolution in MSCs, the CRISPR-Cas system demonstrated inconsistencies that limited its clinical application. In this review, we outline the evolution of MSC research and its applicability, and the progress of the CRISPR-Cas system from its discovery to the most recent clinical trials. We also propose perspectives on how the CRISPR-Cas system may improve the therapeutic potential of MSCs, making it more beneficial and long lasting.